Implementasi Kebijakan Penanggulangan Kemiskinan di Yogyakarta: Tinjauan Penerapan Regulasi dan Otonomi Khusus - Sipahutar, Cornelius; Hitalessy, Yehezkiel Steferd Kristo; Putri, Quinny Azalia (LPPM Universitas Terbuka, 2024)
Despite its abundance of cultural and natural resources, the Special Region of Yogyakarta continues to grapple with poverty. A significant portion of the population in Yogyakarta continues to experience poverty and has not yet completely reaped the advantages of the special autonomy along with its regulations. This study seeks to investigate the issue of poverty and evaluate the efficacy of special autonomy and regulations. A descriptive qualitative method was employed using a desk study to analyze literature from scientific journals, books, and online sources. The findings indicated that the use of special funds and restrictions has not yielded complete efficacy in mitigating poverty. Enhancing collaboration between the government and the community is necessary, and legislation should be tailored to local knowledge and practices. Efforts should be made to enhance the management of dedicated funds with a specific focus on enhancing human resources so as to achieve a more efficient reduction of poverty.